Preparation and Characterization of PCL-PEG-PCL Copolymeric Nanoparticles as Polymersomes for Delivery Hydrophilic Drugs: PCL-PEG-PCL Copolymeric Nanoparticles as Polymersomes - Danafar, Hossein (Iranian Journal of Pharmaceutical Sciences, 2018)
A novel drug delivery system using poly (ε-caprolactone) - poly (ethylene glycol) -poly (ε-caprolactone) (PCL-PEG-PCL) was established in this study. Ceftriaxone (CTX) was encapsulated within PCL-PEG-PCL nanoparticles by a double emulsion technique (w/o/w), leading to creation of ceftriaxone-loaded PCL-PEG-PCL (CTX/PCL-PEG-PCL) polymersomes. The resulting polymersomes were characterized by various techniques such as dynamic light scattering (DLS). The release profile of the CTX from the polymersomes was evaluated. The findings showed the successful formation of spherical CTX/PCL-PEG-PCL polymersomes. The loading efficiency of CTX was 17.50± 1.17 %. The results of DLS showed that the polymersomes have size of 115.7±0.48 nm. In vitro release of CTX from polymersomes was remarkably sustained. The sustained release of drug was hypothetically due to the encapsulation of CTX in core of polymersomes. The results indicate the successful formulation of CTX loaded PCL-PEG-PCL polymersomes. It can be concluded that polymersomes may be considered as an effective treatment strategy to improve the therapeutic effect of CTX in the future.